Co-conversion of lignocellulose-derived glucose, xylose, and aromatics to polyhydroxybutyrate by metabolically engineered Cupriavidus necator. (April 2023) - Weng, Caihong; Tang, Ruohao; Peng, Xiaowei; Han, Yejun
Graphical abstract: Highlights: Corn stover was degraded to glucose, xylose, p -coumaric acid, and ferulic acid. Optimizing CoA-dependent non-β-oxidation pathway enabled growth on ferulic acid. Engineered C. necator could co-utilize glucose, xylose, and lignin-derived aromatics. Corn stover-derived compounds were converted to PHB by engineered C. necator . The maximum yield of PHB from corn stover-derived compounds reached 11.51 g/L. Abstract: Utilization of all major components of lignocellulose is essential for biomass biorefining. Glucose, xylose, and lignin-derived aromatics can be generated from cellulose, hemicellulose, and lignin of lignocellulose degradation through pretreatment and hydrolysis. In present work, Cupriavidus necator H16 was engineered to utilize glucose, xylose, p -coumaric acid, and ferulic acid simultaneously by multi-step genetic engineering. Firstly, genetic modification and adaptive laboratory evolution were performed to promote glucose transmembrane transport and metabolism. Xylose metabolism was then engineered by integrating genes xylAB (xylose isomerase and xylulokinase) and xylE (proton-coupled symporter) in the locus of ldh (lactate dehydrogenase) and ackA (acetate kinase) on the genome, respectively. Thirdly, p -coumaric acid and ferulic acid metabolism was achieved by constructing an exogenous CoA-dependent non-β-oxidation pathway. Using corn stover hydrolysates as carbon sources, the resulting engineered strain Reh06 simultaneously converted all components of glucose, xylose, p -coumaric acid, and ferulic acid to produce 11.51 g/L polyhydroxybutyrate.